MEMBANGUN KESADARAN HUKUM MAHASISWA PPKn UPY DALAM BERLALU LINTAS - T Heru Nurgiansah; Titik Mulyati Widyastuti.; Cep Miftah Khoerudin (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2020)
As the State of the law was supposed to Indonesia Citizens obedient and well behaved on the applicable legislation. Students as agents of change are part of the citizens must obey the rules. Obedience and good legal compliance will only occur if the understanding and knowledge of the law that well and this can only be in the form of through legal education. One of the roles and functions of the civic education was as a legal education. It is aligned with the goals of civic education that is forming good citizens. One of the indicators of good citizens are aware of the law, it means to know, understand, and obey the rule of law, one being traffic rules regulated by law number 22 of the year 2009 about traffic and Road Transport. The purpose of this research is to build awareness of PPKN student from University of PGRI Yogyakarta. This research used the qualitative approach with its data collection techniques in the form of observation, interviews, and documentation. The data analysis techniques through the reduction of data, display data, and verification. The results of this research are valid existence of synchronization between civic education courses with the role of professors and institutions in building awareness of the traffic law PPKN student from University of PGRI Yogyakarta.